Antimicrobial resistance pattern and uropathogens distribution in children visiting a referral hospital in Mogadishu - Abdikarin Ahmed Mohamed; Yavuz Bastug; Cem Senol; Mohamed Muktar Kassim; Abdisalam Abdullahi Yusuf; Abdikarim Hussein Mohamed (Future Science OA)
Aim: Studies concerning epidemiology and drug susceptibility patterns of pediatric urinary tract infection in developing countries are scarce. This study aimed to evaluate the antimicrobial resistance pattern and uropathogens distribution in children. Method: Four-year retrospective study included 840 participants in all pediatric age groups whose urine had been cultured. Results: The prevalence of culture-proven pediatric UTIs was 17.6% (148/840). Escherichia coli was the most common pathogen isolated from the cultures, accounting for (48%, 71/148), followed by Klebsiella pneumoniae (16.2%, 24/148). About 27% of the pathogens had a multidrug-resistant (MDR) pattern. A resistance rate against nitrofurantoin at 24.6%, fosfomycin at 15.2% and trimethoprim-sulfamethoxazole (SMX-TMP) at 79.7% was noted. Conclusion: E. coli and Klebsiella pneumoniae were the most common pathogens isolated.